Mathematical modeling of heat and mass transfer in the extrusion of non-linear polymer compositions and experimental studies of their properties - Trufanova, N.M.; Subbotin, E.V.; Shcherbinin, A.G.; Kazakov, A.V.; Ershov, S.V. (Perm Federal Research Centre Journal, 2017)
Numerical study of extrusion processes of heat-resistant polymer compositions Ftoroplast-4MB, Teflon FEP 345, Tefzel ETFE 280 and polyetherether tone PEEK 151G with unique performance properties was executed. In this work a spatial mathematical model of heat and mass transfer processes of polymer media with nonlinear viscosity was used in conditions of phase transition in the extruder screw channel, taking into account the thermal conductivity of the screw. The rheological and thermal properties of recyclable materials were identified as a result of comprehensive experimental studies. According to the results of numerical studies pressure-flow characteristics, pictures of plug shape changes, temperature field and velocity components in the extruder screw channel were built. It is shown that the productivity of the extruder can depend strongly on the properties of the processed material. It was found that in the processing of high-viscosity polymer compositions Ftoroplast-4MB, Teflon FEP 345 almost in the entire range of changes in the screw rotation frequency, the extruder operates in cooling mode (as opposed to materials PEEK and Tefzel), offsetting the heat energy excess released as a result of dissipation. It is noted that the numerical investigations provide additional possibilities for the study of extrusion processes and can be used as a tool for the development of new screw extruder designs, and the selection of processing rational technological modes for new polymer compositions.